Maternity and art: Claims and specificities facing a heteropatriarchal society - Palomo-Chinarro, Ana Mª; Solà Saña, Sergi (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The exclusion of women from the different areas of participation has led to the need to critically and disruptively confront the precepts established by the dominant majority. Some women artists, based on their position regarding motherhood in art and an attitude with high levels of hostility and irreverence, have contributed to achieving social and professional improvements. Analyzing their vindication strategies, as artists and activists in their lives and in their works, we will see how they have contributed to conquering and consolidating these important achievements.